Analisis Pengaruh Pengembangan Karir Komitmen Organisasi dan Kepempinan Transformasional Terhadap Kinerja Pegawai Pada Kantor Dinas Kelautan dan Perikanan Kabupaten Alor - Imanuel N. Boling Weni (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to determine the effect of career development organizational commitment and transformational leadership on the performance of employee F, which makes up this population of 37 people. namely saturated samples of data collection using techniques namely observation, interviews, and documentation studies. The data is then analyzed using the t test to find out partially and the f test to determine the effect simultaneously. This research uses population primary data and the sample is employees at the District Marine and Fisheries Service Office Alor which amounted to 37 people. And the sampling technique in this study is a saturated sample. The statistical method used in this study is multiple linear regression. The results of this study indicate that: (1). partially the career development variable has a significance value of 0.001 or 0.1% where this value is smaller than the alpha value of 0.05 or 5% so that the results of this study accept H1 which states that the career development variable partially has a positive effect on employee performance at Alor Regency Maritime Affairs and Fisheries Service Office. (2). partially the organizational commitment variable has a significant value of 0.023 or 2.3% where this value is smaller than the alpha value of 0.05 or 5% so that the results of this study accept H2 which states that the organizational commitment variable partially has a positive effect on employee performance at Alor Regency Maritime Affairs and Fisheries Service Office (3). partially the transformational leadership variable has a significant value of 0.001 or 0.5% where this value is smaller than the alpha value of 0.01 or 5% so the results of this study accept H3 which states that the transformational leadership variable partially has a positive effect on employee performance at the Maritime Service Office And Fisheries of Alor Regency. (4). simultaneously the career development variable organizational commitment and transformational leadership has a significant value of 0.000 or 0.00% where this value is smaller than the alpha value of 0.05 which is 5% so that the results of this study simultaneously accept H4 which states that the variable career development organizational commitment and transformational leadership has an effect positively on the performance of employees at the Alor Regency Maritime Affairs and Fisheries Service Office. (5). The magnitude of the influence of organizational commitment and transformational leadership career development variables on employee performance at the Maritime Affairs and Fisheries Office of Alor Regency is 82.6%, this study simultaneously received H5.